c - Francisco, Jehan, et.al. ([Tagbilaran City, Bohol]: [Holy Name University], 2023)
Abstract: The study aimed to assess the effectiveness of home-based laboratory experiments of BSED Science and BS Biology students of Holy Name University enrolled in Genetics subject in the first semester of the Academic year 2021-2022. This study sought to answer the effectiveness of the components of home-based laboratory experiments in terms of: alternative materials, consultations, instructional materials, references, laboratory experiment performance, and learning outcome. The study also measured the significant difference of the effectiveness between the components of home-based laboratory experiments and made use of the descriptive survey research design with respondents of seventeen (17) students from BSED Science and BS Biology. Frequency percentage of results and t-test was used in tabulating important information and researchers'-made survey questionnaire. Findings revealed that household kitchen items are widely used and cost less for alternative materials, consultations are possible in terms of student-peers and student-teachers' and it could also comprehend and improvise materials at home through effective instructional materials with different sources thus, students learn scientific principles. There is no significant difference in terms of the effectiveness between the components of home-based laboratory experiments of the BSED Science and BS Biology students. Therefore, the researchers generally concluded that the effectiveness in enabling students to learn in home-based laboratory experiments depends on the flexibility, openness, and opportunity to find ways and improve home-based laboratory experiments. To promote and continuing the ways and practices obtained throughout home-based laboratory experiments in Genetics class is what the researchers generally recommend.
CoED